MLL2 mosaic mutations and intragenic deletion–duplications in patients with Kabuki syndrome. (18th September 2012) - Banka, S; Howard, E; Bunstone, S; Chandler, KE; Kerr, B; Lachlan, K; McKee, S; Mehta, SG; Tavares, ALT; Tolmie, J; Donnai, D
<x xml:space="preserve">Abstract</x> Kabuki syndrome (KS) is a rare multi‐system disorder that can result in a variety of congenital malformations, typical dysmorphism and variable learning disability. It is caused by MLL2 point mutations in the majority of the cases and, rarely by deletions involving KDM6A. Nearly one third of cases remain unsolved. Here, we expand the known genetic basis of KS by presenting five typical patients with the condition, all of whom have novel MLL2 mutation types– two patients with mosaic small deletions, one with a mosaic whole‐gene deletion, one with a multi‐exon deletion and one with an intragenic multi‐exon duplication. We recommend MLL2 dosage studies for all patients with typical KS, where traditional Sanger sequencing fails to identify mutations. The prevalence of such MLL2 mutations in KS may be comparable with deletions involving KDM6A. These findings may be helpful in understanding the mutational mechanism of MLL2 and the disease mechanism of KS.